Effect of Cell Growth and Proliferation Factors (EGF/PDGF Signaling Pathway) on the Etiopathogenesis of Intrauterine Growth Restriction - Serhan Can İşcan; Erhan Demirdağ; Melek Yaman; Emin Ümit Bağrıacık; Merih Bayram (Gazi Medical Journal)
Objective: It is likely that the subgroups of the epidermal growth factor/platelet-derived growth factor (EGF/PDGF) signaling pathway play a role in the etiopathogenesis of intrauterine growth restriction (IUGR). This study was planned to understand the molecular genetic level of apoptosis in IUGR. Method: The EGF/PDGF signaling pathway gene profile (40 genes) was investigated using a real-time reverse transcriptase-polymerase chain reaction. The gene expressions of the IUGR group were compared both individually and as a group. Individual gene differences were also evaluated. The genes related to cell survival and growth, which include the gene groups of apoptosis, cell cycle, cell differentiation, cell growth, cell motility, and cell proliferation, were investigated using microarray technology. Results: Parity, gestational age at delivery, and APGAR scores at the first and fifth minutes were not significantly different between the IUGR and control groups. However, the women in the IUGR group were younger and slimmer. PRKCA was the only gene with a significant difference in expression between the IUGR and control groups. Nevertheless, individual differences were detected in gene expression associated with cell cycle, differentiation, growth, motility, proliferation, and apoptosis. Conclusion: Variations in gene expression during pregnancy cause changes in placental and fetal development by affecting apoptosis and cellular events at different levels. The genetic causes of IUGR can be revealed by investigating these metabolic pathways. This study differs from previous IUGR studies, which focused on one or a few genes, because all the gene groups in the EGF/PDGF pathway that may be associated with IUGR were investigated.